Dietary soy protein reverses obesity-induced liver steatosis and alters fecal microbial composition independent of isoflavone level - Hakkak, Reza; Korourian, Soheila; Li, Wei; Spray, Beverly; Twaddle, Nathan C.; Randolph, Christopher E.; Børsheim, Elisabet; Robeson II, Michael S. (Frontiers in Nutrition, 2024)
Non-alcoholic fatty liver disease (NAFLD)Metabolic dysfunction-associated steatotic liver disease (MASLD) is a major public health concern that is exacerbated by the obesity pandemic. Dietary interventions have the potential to alleviate obesity-associated NAFLDMASLD through variable mechanisms, including optimizing the gut microbiota. Previously, we reported that soy protein concentrate (SPC) with low or high levels of isoflavone (LIF or HIF) protected young obese Zucker rats from developing liver steatosis. The current study was designed to test whether SPC-LIF and SPC-HIF diets would reverse liver steatosis and alter fecal microbial composition in adult obese Zucker rats with existing steatosis. Six-week-old male obese Zucker rats (n = 2826) were fed a casein control diet (CAS) for 8 weeks and 7 rats were randomly selected and sacrificed to confirm liver steatosis. The remaining rats were randomly assigned to receive CAS, SPC-LIF, or SPC-HIF diet (n = 6 -7/group) for an additional 10 weeks. Compared to CAS diet, feeding SPC-LIF and SPC-HIF diets resulted in significantly lower liver weight, liver steatosis score, and liver microvesicular score (p < 0.05), but did not lead to difference in body weight, liver macrovesicular score, serum ALT, or serum AST. Isoflavone levels (e.g. LIF vs. HIF) did not affect any of these measurements except in the SPC-HIF group, which had an additional decrease in liver weight (p < 0.05) compared to the SPC-LIF group. The SPC-HIF group also had significantly higher levels of allthe aglycone forms of daidzein, genistein, and equol as well as theand total levels of daidzein, genistein, and equol compared to SPC-LIF or CAS diet fed rats (p < 0.05). The distribution of microbial communities based on measures of beta diversity of both SPC-LIF and SPC-HIF groups were significantly different to that of the CAS group (p ≤ 0.005). Conversely, aAlpha-diversity did not differ between any of the groups. When tTakenTaken together, dietary soy protein can reverse liver steatosis in adult Zucker rats, and the reversal of steatosis is accompanied by alterations in gut microbial composition.